Uji Daya Hambat Jamur Antagonis terhadap Jamur Penyebab Penyakit Utama pada Tanaman Ubi Jalar Ungu (Ipomoea batatas (L.)) Secara In Vitro - NI WAYAN EKA SUDI ARTI; NI WAYAN SUNITI; I DEWA PUTU SINGARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
In Vitro InhibitionTest of Antagonistic Fungi on Pathogenic Fungi of the Main Diseases in Purple Sweet Potatoes (Ipomoea batatas (L.) Purple sweet potato is a plant commodity that is in great demand by people today. Peringsari Village, Selat Sub-district, Karangasem Regency is one of the sweet potato-producing areas in Bali. The purple sweet potato plant developed in Peringsari village shows many symptoms of the disease on the stems and leaves of the plant. The cause of the main disease of this plant is not yet known, but the symptoms shown are such as attack by pathogenic fungi. This purple sweet potato disease does not get much attention from farmers because it is considered to have no effect in terms of the quantity and quality of sweet potatoes. The purpose of this study was to determine the main pathogens that cause disease in purple sweet potato plants and to determine which antagonistic fungi are effective in suppressing the growth of pathogens in purple sweet potato plants in Peringsari Village, Selat District, Karangasem Regency. This research was conducted in Peringsari Village, Selat Subdistrict, Karangasem Regency for sampling to be continued at the Plant Disease Laboratory, Faculty of Agriculture, Udayana University. Field observations, isolation, and morphological identification showed that the main disease-causing pathogen in purple sweet potato was the fungus Fusarium sp. and the antagonistic fungi that can control pathogenic fungi in vitro are Trichoderma asperilum, Trichoderma harzianum, Trichoderma koningii, and Trichoderma viride.